Identification of stress proteins in Vibrio parahaemolyticus and detection of their antigenic properties - Rahman, Farhin (BRAC University, 2017)
A Dissertation Submitted in Partial Fulfillment of the Requirements’ for the Degree of Master of Science in Biotechnology 2014.